2004
DOI: 10.1111/j.1471-0528.2004.00080.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of residual urinary incontinence following successful repair of obstetric vesico‐vaginal fistula using a fibro‐muscular sling

Abstract: Obstetric vesico-vaginal fistula remains a significant cause of female urinary incontinence worldwide. Approximately 2 million women suffer from this condition, perhaps many more, most of whom are in Africa. Very few centres are treating these patients, and although success rate in the closure of the fistula is high, up to 92%, this does not necessarily equate to a cure. A significant proportion of women remains with urinary incontinence. Little is known about the nature of this incontinence, and even less is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 9 publications
1
53
0
Order By: Relevance
“…Among these determinants, fibrosis and urethral involvement have been identified by other authors [4] [9] [18], although some authors such as Barone [4] and Browing [19] do not recognize the importance of fistula size among the determinants of the success of the cure, however they agree on the size of the bladder, consequence of the size of the latter as an important element in this cure.…”
Section: Discussionmentioning
confidence: 99%
“…Among these determinants, fibrosis and urethral involvement have been identified by other authors [4] [9] [18], although some authors such as Barone [4] and Browing [19] do not recognize the importance of fistula size among the determinants of the success of the cure, however they agree on the size of the bladder, consequence of the size of the latter as an important element in this cure.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Few studies have investigated the nature of this residual incontinence urodynamically, those that have concluded that it is often stress urinary incontinence. 4 These women are a particularly difficult group to treat as they are present in areas of very limited medical resources and have a complicated, often poorly understood, pathology.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence is variably reported to affect between 8 and 33% of women after repair of their fistula. 1,2 A recent survey of 2000 patient notes in the Addis Ababa Fistula Hospital showed 26% of women suffering residual incontinence in the immediate postoperative period (E. Boyd and A. Browning, unpubl).…”
Section: Introductionmentioning
confidence: 99%
“…The fistulas were classified using the Waaldijk classification of vesico-vaginal fistula [4] ( Table 1). The examination consisted of a sterile speculum examination of the vagina, estimation of urethral length utilizing Foley catheter insertion, and estimation of bladder capacity using a graduated uterine sound in the bladder [5]. This technique, described by Waaldijk, utilized a graduated uterine sound to measure the distance between the urethral meatus and the bladder dome by subtracting the urethral length (centimeter distance from external urethral meatus to the inflated Foley balloon).…”
Section: Diagnostic and Surgical Techniquesmentioning
confidence: 99%